Yearbook of the International Law Commission 2000, Vol. II, Part 1 - United Nations (United Nations, 2010)
This volume contains the summary records of the meetings of the fifty-second session of the Commission with the corrections requested by members of the Commission and such editorial changes as were considered necessary. The issues discussed at that session included: State responsibility; unilateral acts of States; nationality in relation to the succession of States; prevention of transboundary damage from hazardous activities; diplomatic protection; reservations to treaties and long-term programme of work of the Commission.